Fluorescence guided surgery in liver tumors: applications and advantages - Rossi, Giorgio; Tarasconi, Antonio; Baiocchi, Gianluca; de' Angelis, Gian Luigi; Gaiani, Federica; Di Mario, Francesco; Catena, Fausto; Dalla Valle, Raffaele (Acta Biomedica Atenei Parmensis, 2018)
The use of fluorescence-guided surgery for benign and malignant hepatobiliary (HPB) neoplasms has significantly increased and improved imaging methods creating new interesting perspectives. A major challenge in HPB surgery is performing radical resection with maximal preservation of the liver parenchyma and obtaining a low rate of complications. Despite the developments, visual inspection, palpation, and intraoperative ultrasound remain the most utilized tools during surgery today. In laparoscopic and robotic HPB surgery palpation is not possible. Fluorescence imaging enables identification of subcapsular liver tumors through accumulation of indocyanine green (ICG), after preoperative intravenous injection, in cancerous tissues of hepatocellular carcinoma and in noncancerous hepatic parenchyma, around intrahepatic cholangiocarcinoma and liver metastases, and it can also be used for visualizing extrahepatic bile duct anatomy and hepatic segmental borders, increasing the accuracy and the easiness of open and minimally invasive hepatectomy.